Use of computer support as motivation for studying language information units for carrying out professional maritime activities in communication conditions - Tatyana Panayotovna Avanesova; Elena Yuryevna Zadorozhnaya; Tatyana Dmitrievna Kurshakova; Nonna Ivanovna Kozlova (Вестник Майкопского государственного технологического университета)
The relevance of studying English marine terminology is due to work with original materials as part of professional activities in negotiating with coast stations, port authorities and various services of foreign countries. One has to deal with a huge number of information units (IU) required in communication. The problem consists in a comparative consideration of the language terminological processes in professional maritime activities (PMA). The aim of the study is to motivate the study of language IU using computer support for the implementation of PMA in communication. The research methods include testing of experimental groups in training and control modes, using “STEP” computer training system; testing control groups using paper media. IMO standard phrases are the language basis of the test tasks. As a result of the scientific research the possibility of studying IU in a short period of time using a computer program in training and control modes has been presented. It has been experimentally revealed that computer support promotes the development of reflective personality traits through inducing self-assessment of the ability to rely on the IU studied and organizing one's own actions for their assimilation; comprehension and formation of one’s own attitude to IU and motivation for their study; forecasting mutual understanding in relations with a possible partner based on the material being studied; current self-organization of the sequence of actions of perception, reproduction and rethinking of IU and self-assessment of their assimilation. This leads to high motivation of the learning process in order to master professional activities.